Gemini AI Utilization Training for English Language Learning at SMA IT Iman Syafi'i Cendikia - Sri Yuliani; Shalawati Shalawati; Dicki Hartanto; Endang Istikomah; Yusti Elida; Resy Oktadela; Angela Agusta; Muhammaad Iqbal (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The purpose of Gemini AI utilization training for English language learning was to give a service in socialization in Pondok Pesantren MoU and UIR. The goal of in this socialization was to deliver process of socialization, namely socializing values, knowledge, and skills in life. Mufida (2018) said that learning is a real situation for the citizens’ improvement in iman and takwa so they can live without changing address future threats and challenges. Questionnaire was used to measure the satisfactory activity during PkM and 27 female students involved during one day training program. As for SMA IT Iman Syafi’I Cendikia itself, they have future wish that the progress of young generation for having the paradigm that the success of a student is influenced by educators who teach in schools, especially in using modern technology. Gemini AI became one of AI tools of the program was delivered during the activities of PkM. The result of this PkM activity was motivating the students as the data result from questionnaire that the average satisfaction was high as amount 92,67%, so as summary that the implementation of PkM was successful in SMA IT Iman Syafi’I Cendikia.